Android based karateka physical test instrument - Purba, Pangondian Hotliber; Siahaan, David; Ardilla, Rafika; Kasih, Indra; Manalu, Nimrot (Edelweiss Applied Science and Technology, 2024)
This study aims to develop an android-based karate athlete physical test instrument. This study uses the Research and Development research method, namely the ADDIE development model, which includes the Analyze, Design, Develop, Implement, and Evaluate stages. This study involved several experts consisting of karate experts, physical standard experts, linguists, and media experts to validate the developed instrument. In addition, this study also involved a number of karate athletes in the implementation and evaluation process. The research data collection technique was carried out through a questionnaire. From the five stages carried out, this study succeeded in producing an android-based karate athlete physical test instrument according to the needs in the field. From the evaluation of the suitability of the android-based karate athlete physical test instrument based on the assessment of karate experts, physical standard experts, linguists, and media experts, it was found that the developed instrument was declared feasible for use. These results are also supported by the results of trials on athletes in small groups and large groups also stating that the android-based karate athlete physical test instrument developed is feasible for use. Based on these results, this study concludes that the android-based karate athlete physical test instrument developed is ready for use. The detailed results of the analysis, design, develop, implement, and evaluate stages are explained in this article.